Dimensions of effective teaching - Manandhar, Juju Bhai (Chaitanya Research Journal, 2024)
This article explores findings concerning effective teaching. The term 'effective teaching' has been used in this article in a broader sense rather than simply accepting teacher behavior, or what teachers are seen to do in the classroom. It summarizes the vast literature related to effective teaching. This review summarizes effective teaching into five dimensions: supportive learning environment, academic expectations, scaffolding learning, clarity and adoption; and integration of Information and Communication Technology (ICT) in the teaching-learning process.